OWA operators in data modeling and reidentification. - Torra, V. (IEEE Transactions on fuzzy systems)
This paper is devoted to the application of aggregation operators and to the application of ordered weighting averaging (OWA) operators to data mining. In particular, we consider two application of OWA operators in this field: model building and information extraction. The latter application is oriented to the reidentification procedures.